Evaluasi Kegiatan Rehandling Batubara dan Kesesuaian Rencana Crushing pada ROM Port Area 2 PT Multi Harapan Utama - Nirwana Putri; Windhu Nugroho; Tommy Trides; Henny Magdalena; Harjuni Hasan (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
In rehandling activities In coal processing activities, mechanical tools such as crushers are needed to obtain production results in accordance with the company's desired targets according to the crusher target, therefore in processing it is necessary to carry out precise calculations, so that the ability of the tool (crusher) and know what things greatly affect the production processing process, so that it can be used optimally and has a high efficiency value for optimal production. Therefore, it is necessary to evaluate the results of the crusher production and the productivity of the support unit during rehandling activities in achieving the production target at ROM Port Area 2 in order to adjust the ability of the tool and other influencing factors with the crusher production target desired by the company. Actual rehandling productivity meets the crusher production plan target of 1100tph. Productivity in each zone with DT wheel 10, namely zone H there are 2 of 120,620 tph and 154,935 tph, zone L of 135,351 tph, zone M of 138,313 tph, zone I of 189,709 tph. And constraints on the crusher during a month that also affect obstacles in rehandling include schedule time with a total time of 176.72 hours, breakdown time with a total time of 4.84 hours, unscheduled time with a total time of 154.62 hours.